POSITION AND PROTECTION OF ASSOCIATION RIGHTS SECURITY UNIT IN HUMAN RIGHTS PERSPECTIVE ACCORDING TO THE BASIC STATE LAW OF THE REPUBLIC OF INDONESIA YEAR 1945 - Edi Candra; Azmi Azmi; Anne Gunawati (Universitas Muhammadiyah Tangerang, 2021)
The rights and obligations in the world of labor have been regulated in the labor law, including the right of association which must be given to every worker to associate as stated in Law Number 21 of 2000 concerning Trade Unions / Labor Unions Article 28 and Article 43. In addition, problems arise when the Indonesian National Police Headquarters on behalf of the Indonesian National Police Chief through the Head of the Security Maintenance Agency issues Circular Letter Number; B/194/I/201/Baharkam concerning: Security Guards are Not Members of Trade Unions. In Article 5 of the Circular, it is stated that